Memoirs of the Emirates. (2012)
"'Memoirs of the Emirates' offers a kaleidoscopic view of life and times in the Emirates in the 50s, 60s and 70s of the last century through vivid reminiscences and recollections. Amply illustrated with 'never before seen' vintage photographs, the book takes its readers on a photographic journey over the last 50 years"--Forward.
"Proceedings of the Seminar on memoirs of the Emirates through oral narratives"--Page facing title page.
At head of title: National center for documentation and research, Ministry of presidential affairs.
Seminar held in 2010--Page 9.